Romeo and Juliet - Shakespeare, William, 1564-1616 (Unley, South Australia : Bibliologica Press, 2020)
Early in William Shakespeare's career, he wrote the romantic tragedy “Romeo and Juliet”. It is a timeless tale of two young star-crossed lovers. Arguably, the portrayal of the two title characters' deaths and the subsequent reconciliation of their feuding families is what stirs powerful emotions in readers and audiences alike. Hence, Shakespeare's play has become one of the most popular plays to be studied and performed. Scholars consider the play to have been written between 1591 and 1595, but first published in 1595. Yet, in modern times, "Romeo and Juliet" remains a favorite for adaptation by playwrights, and screen writers, as well as musical and opera directors. It is not surprising that this archetypal story of young love forms part of the required reading in many high school and college English classes.
"This classic reprint published by Bibliologica Press ..."--Colophon.
Keywords: Shakespeare, William, -- 1564-1616; Juliet -- (Fictitious character) -- Drama; Romeo -- (Fictitious character) -- Drama